Peran Dosen Mata Kuliah Pendidikan Agama Islam Dalam Membangun Karakter Islami Mahasiswa Universitas Teknologi Sumbawa - Utama, Abdul Alimun; Kurniawati, Luthfiyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to understand and know the role of lecturers of Islamic Religious Education (PAI) in building character education in Sumbawa University of Technology students. This type of research is qualitative descriptive research using data analysis, namely the Spradley model and taking the research location in the campus environment of Sumbawa University of Technology. The results of this study show that the role of lecturers in building student character education through Islamic Religious Education courses at Sumbawa University of Technology (UTS) is taken with several lecturer roles, namely: (1) Exemplary, the stage where lecturers touch the emotional aspects of students' souls and hearts to be consistent in carrying out orders and prohibitions in religion in everyday life; and (2) Inspirator, is the peak stage in building student character, namely raising the spirit of learning to pursue potential and spectacular for students; (3) Motivator, is the ability of teachers / lecturers to awaken spirit, work ethic, and extraordinary potential in students; (4) Dynamicator, is a locomotive that really pushes students towards the goal with high speed, intelligence, and wisdom; and (5) Evaluator, is a vehicle to review the effectiveness, efficiency, and productivity of a program. Based on observations and interviews, the Islamic Education course at UTS has succeeded in building students' character for the better.